# FinalExam_Feb_2006_Answers - Θ µα 1(α p p[x0 sin θ(z0...

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Θ µα 1 (α) p p [x0 sin θ + (z0 − h) cos θ] + [−x0 sin θ + (z0 + h) cos θ] 4π 0 R3 4π 0 R 3 Φ(x0, z0 ) = oπoυ R = [x2 + (z0 − h)2 ]1/2 , 0 R = [x2 + (z0 + h)2 ]1/2 0 (β) σ(x) = 3ph(−x0 sin θ + h cos θ) 2π(x2 + h2 )5/2 (γ) T = −ˆy i p2 sin 2θ 64π 0 h3 Θ µα 2 (α) Φ1 (φ) =A1 φ + B1 (0 ≤ φ < φ1 ) Φ2 (φ) =A2 φ + B2 (φ1 ≤ φ < φ0 ) oπoυ A1 = 2U ( 2 − 1 )φ1 + 1 φ0 , B1 = 0, A2 = 1U ( 2 − 1 )φ1 + 1 φ0 , B2 = ( 2 − 1 )U . ( 2 − 1 )φ1 + 1 φ0 (β) E1 = − 1 i A1ˆφ , rT E2 = − 1 i A2ˆφ. rT (γ) ρb1 = 0, ρb2 = 0, σb (φ1 ) = (A1 − A2 ) 0 , rT σb (φ = 0+ ) = ( 1 − 0 )A1 , rT (δ) σ(φ = 0+ ) = − A1 1 , rT σ(φ = φ− ) = + 0 A2 2 . rT σb (φ− ) = − 0 ( 2 − 0 )A2 , rT Θ µα 3 (α) σ0 a( 1 + σ0 Φ2 (x, y) = a( 1 + Φ1 (x, y) = (β) σ0 1 + σ0 E2 (x, y) = − ( 1+ E1 (x, y) = − ( 2) 2) 2) 2) eax sin(ay) e−ax sin(ay) (−∞ < x ≤ 0) (0 ≤ x < +∞) i i eax [sin(ay)ˆx + cos(ay)ˆy ] i i e−ax [− sin(ay)ˆx + cos(ay)ˆy ] (γ) E(x, y) = −ˆy i σ0 ( 1+ 2) e−a|x| (−∞ < x ≤ 0) (0 ≤ x < +∞) (−∞ < x < +∞) Θ µα 4 (α) H= 1 4π 2π φ =0 a rT =b K(φ ) × ˆR (rT , φ ) i rT dφ drT R2 oπoυ ˆR = 1 [(rT 0 cos φ0 − rT cos φ )ˆx + (rT 0 sin φ0 − rT sin φ )ˆy + z0ˆz ] = axˆx + ayˆy + azˆz , i i i i i i i R 2 2 R = [rT 0 + rT2 − 2rT 0 rT cos(φ0 − φ ) + z0 ]1/2, K × ˆR = ˆx (az K0 cos φ ) + ˆy (az K0 sin φ ) + ˆz (−K0 sin φ ay − ax K0 cos φ ). i i i i (β) √ b a + a2 + z 2 ˆz K0 − √ a √ H(0, 0, z) = i +√ + ln 2 a2 + z 2 b2 + z 2 b + b2 + z 2 ...
View Full Document

{[ snackBarMessage ]}

### Page1 / 2

FinalExam_Feb_2006_Answers - Θ µα 1(α p p[x0 sin θ(z0...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online